The Role of the Principal as a Motivator in Optimizing Teacher Performance at PAUD Qur'an Al-Jazary Surakarta - Indah Nur Choiriyah; Suyatman, Suyatman (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
The development of an educational institution lies in the leadership of the principal, where the principal is responsible for the ongoing teaching and learning activities and developing programs and potential of students and teachers in an organization at school. This study aims to describe the role of the principal as a motivator in optimizing the performance of educators at Paud Qur'an Al Jazary Surakarta. The approach used in this study is qualitative with descriptive methods. Data collection was carried out through interviews, observations, and document analysis. The findings of the study indicate that the principal has a crucial role in optimizing teacher motivation through the creation of a suitable physical environment, a conducive working atmosphere, the application of discipline, providing motivation, awards, and the provision of learning resources. Although there are several aspects, such as awards and the provision of learning media that still need to be improved. However, overall the role of the principal as a motivator has had a positive influence on improving the performance of educators.